The impact of virtual experience on visiting tourism destination intention - Taufiq Hidayat; Nova Riana (Jurnal Pariwisata Pesona, 2023)
The Covid-19 pandemic had changed the people’s behavior and activities in many aspects of living. The government policy of physical distancing in the entire Indonesia impacted activities of people in many sectors, including tourism. In response to this, some Travel Agencies, Destination Management, and Tour Guides had an initiative to launch Virtual Tours as an alternative to organize a tour without mobility. For most of people, Virtual Tours are a new experience. They can visit many kinds of tourism destinations while stay at home. When this phase of pandemic end, this could be a “new normal” people, where Virtual Tours become a first reference for tourists, before they decide to visit a tourism destination. This research aimed to measure how much the concept of Virtual Tour influences the intention of visiting a tourism destination, and how was the potency to recommend it to their friends. The authors used the tourist experience approach as a perspective to gain informations about the tourists experience in enjoying Virtual Tours and how is their interests of visiting. How the experience of Virtual Tours influenced the intention of visiting to the destination they enjoyed in virtual tour, and moreover recommend the destination to their friends, to get the same experience. Through the explanation method to explain the relation between the two variables in this research, the authors used the data gained from a questionnaire from 44 respondents with purposive sampling technique. Analysis of the data used in this study is a simple linear regression analysis and described descriptively. The result of the coefficient of determination from the role of virtual tours experience on interest in visiting tourist destinations is 0.420. This value shows that 42% of interest in visiting tourist destinations is influenced by the experience of virtual tours, while the remaining 58% is determined by other factors outside of this study.